Quality Improvement Efforts in Pre-Analytical Phase - Osman Sianipar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
In a clinical laboratory services pre-analytical phase has plays an important role in term of quality and patient safety. Pre-analytical phase is a phase before analyzing sample in laboratory which  includes  patient preparation, sampling, labeling, sample transportation, sample storage,  and preservation of samples that might influence the laboratory results. In this phase it involves interaction between patient, doctor, laboratory personels, and other staff outside the laboratory. Therefore, it could be assumed that in this phase many sample are collected, many laboratory tests are requested, many individuals are involved and therefore laboratory errors might be occured. Laboratory errors can occur either in pre-analytical, analytical, or post analytical phases but the most frequently errors occur in pre-analytical phase. In this article, quality improvement efforts in pre-analytical phase will be discussed in order to minimize pre-analytical error.